Characteristics associated with successful adjustment to supervision - MacKenzie, Doris L. (Criminal justice and behavior, 1992)
Offender adjustment during community supervision was examined in two studies. Study 1 examined the positive social activities of parolees and probationers during community supervision. Shock parolees engaged in more positive social activities in comparison to regular parolees, probationers, and dropouts; however, once the intensity of supervision was controlled, differences among groups in positive social activities disappeared. Regardless of the supervision intensity, offenders who were younger, younger at first arrest, and non-White adjusted less well to community supervision. The second study examined the characteristics of offenders who successfully completed two phases of a shock incarceration program. Those who completed the in-prison phase had higher IQs and longer sentences, and believed more strongly in their ability to control events. Shock graduates who succeeded during the first year of parole supervision were older and were less likely to have a criminal history. They were also more apt to be employed and were involved in more positive activities during the first month of supervision